Improving Incubator Manufacturing Performance Through RPW-Based Line Balancing and Constraint Management - Fredy Sumasto; Febriza Imansuri; Indra Rizki Pratama; Abdul Wahid Arohman; Sanurya Putri Purbaningrum (International Journal of Industrial Engineering and Engineering Management, 2026)
In the regulated field of medical device manufacturing, optimizing production efficiency without compromising compliance is critical, particularly for small and medium-sized enterprises (SMEs) operating in resource-constrained environments. This study addresses production inefficiencies in the assembly of the TSN 89 TR neonatal incubator at PT Tesena Inovindo, an Indonesian manufacturer, by implementing an integrated improvement framework. The approach combines Lean Manufacturing for process stabilization, the Ranked Positional Weight (RPW) method for line balancing, and the Theory of Constraints (TOC) for bottleneck resolution. Time study data were collected across 30 cycles per task to ensure reliable estimates of average cycle times, based on the Central Limit Theorem. The initial production system exhibited unbalanced workloads, high idle time, and frequent work-in-process (WIP) accumulation. After reconfiguration, the number of workstations was reduced from ten to eight, the cycle time decreased by 23.8%, and daily output increased from four to six units. Line efficiency improved from 67.2% to 89.5%, with idle time dropping from 32.8% to 10.5%. These gains were achieved without automation or additional labor, relying solely on empirical task analysis and workflow redesign. The study offers a replicable, low-cost framework for optimizing semi-manual assembly lines in regulatory environments. It demonstrates that substantial performance improvements can be achieved through structured, data-driven interventions, making it particularly valuable for SMEs in emerging markets seeking ISO 13485 compliance and operational excellence.